NERACA AIR SITU CIKARET DAN SITU KABANTENAN DI KABUPATEN BOGOR MENGGUNAKAN PEMODELAN HIDROLOGI SWAT - Nugraheni, Claudia Tyas; Pawitan, Hidayat; Purwanto, Yanuar Jarwadi; Ridwansyah, Iwan (LIMNOTEK - Perairan Darat Tropis di Indonesia, 2019)
Bogor regency which is located in the middle of the Ciliwung basin centered in Cibinong city is experiencing rapid urban development. However, with the rapid urban development, most of these small lakes in either disappear or in degraded conditions. In this area presently still maintain 95 urban small lakes or locally known as ?situ?. Situ has multifunction such as water retention for flood mitigation, irrigation for urban agriculture, fisheries, water sport activities, and ecotourism. The objective of this study was to analyze the water balance of situ. The model was calibrated and validated on the Kampung Kelapa river gauge with manual calibration. The Soil Water Assesment Tool (SWAT) is a hydrological model designed to predict the impact of land use and management on water, sediment and agricultural chemical yields in watersheds, The model was applied to Situ Kabantenan and Cikaret for modeling of the hydrological water balance. The SWAT model simulation was done for the periods of 2008?2015 while it used land use information in 2014. The Calibration was done in 2014 and the validation in 2013, the R2 and Nash Sutcliffe Efficiency (NSE) of the calibration were 0,58 and 0,55 respectively and the validations were 0,54 and 0,49 respectively. The monthly average of volume of Situ Kabantenan and Situ Cikaret from the simulation were 136,955 m3 and 508,907 m3, respectively. The annual inflow of Situ Cikaret was 24,693,822 m3/year and outflow was 25,177,593 m3/year, precipitation was 648,520 m3/year, evaporation was 166,543 m3/year, delta storage 1,794 m3/year, respectively. The average inflow discharge of Situ Cikaret (2008?2015) were 0.78 m3/s and outflow discharge was 0.80 m3/s. The water balance results showed that both sites were in good condition since they have never passed the emergency spillway, but their function needs to be optimized as a flood controller in the Ciliwung Watershed. This study also showed that the SWAT model can be utilized as a potential monitoring tool, especially for small urban lakes as water reservoirs.